Brisket Disease Is Associated with Lower Volatile Fatty Acid Production and Altered Rumen Microbiome in Holstein Heifers - Naren Gaowa; Kevin Panke-Buisse; Shuxiang Wang; Haibo Wang; Zhijun Cao; Yajing Wang; Kun Yao; Shengli Li (Animals, 2020)
Brisket disease is heritable but is also associated with non-genetic risk factors and effects of the disease on the rumen microbiome are unknown. Ten Holstein heifers were exposed to the plateau environment for three months and divided into two groups according to the index of brisket disease, the mean pulmonary arterial pressure (mPAP): brisket disease group (BD, n = 5, mPAP > 63 mmHg) and healthy heifer group (HH, n = 5, mPAP < 41 mmHg). Rumen fluid was collected for analysis of the concentrations of volatile fatty acids (VFAs). Extracted DNA from rumen contents was analyzed using Illumina MiSeq 16S rRNA sequencing technology. The concentration of total VFA and alpha-diversity metrics were significantly lower in BD group (p < 0.05). Ruminococcus and Treponema were significantly decreased in BD heifers (p < 0.05). Correlation analysis indicated that 10 genera were related to the mPAP (p < 0.05). Genera of Anaerofustis, Campylobacter, and Catonella were negatively correlated with total VFA and acetic acid (R < −0.7, p < 0.05), while genera of Blautia, YRC22, Ruminococcus, and Treponema were positively related to total VFA and acetic acid (R > 0.7; p < 0.05). Our findings may be a useful biomarker in future brisket disease work.